statement is true!
Step-by-step explanation:
Here we have , The circle[tex](x-2)^2+(y-3)^2=16[/tex] intersect y-axis. We need to find that this statement is true or false . We have the following equation of circle :
[tex](x-2)^2+(y-3)^2=16[/tex]
Now, In order to say that circle intersect y-axis , we have x=0 , Let's find out value of y for this:
[tex](x-2)^2+(y-3)^2=16[/tex]
⇒ [tex](0-2)^2+(y-3)^2=16[/tex]
⇒ [tex]4+(y-3)^2=16[/tex]
⇒ [tex](y-3)^2=12[/tex]
⇒ [tex]\sqrt{(y-3)^2}=\sqrt{12}[/tex]
⇒ [tex]y-3 = \pm 2\sqrt{3}[/tex]
⇒ [tex]y=3 \pm 2\sqrt{3}[/tex]
Therefore circle[tex](x-2)^2+(y-3)^2=16[/tex] intersect y-axis at two points [tex](0 , 3+2\sqrt{3})[/tex] and [tex](0 , 3-2\sqrt{3})[/tex]. And so statement is true!